Organic writing assessment: dynamic criteria mapping in action - Broad, Bob, author; Adler-Kassner, Linda, author; Alford, Barry, author; Detweiler, Jane, author; Estrem, Heidi, author; Harrington, Susanmarie, author; McBride, Maureen, author; Stalions, Eric, author; Weeden, Scott, author; Utah State University Press, publisher (Colorado State University. Libraries, 2009)
Organic Writing Assessment represents an important step in the evolution of writing assessment in higher education. This volume documents the second generation of an assessment model that is regarded as scrupulously consistent with current theory it shows DCM's flexibility, and presents an informed discussion of its limits and its potentials.
1. Organic Matters: In Praise of Locally Grown Writing Assessment / Bob Broad 2. The Journey is the Destination: The Place of Assessment in an Activist Writing Program -- Eastern Michigan University / Linda Adler-Kassner and Heidi Estrem 3. DCM as THE Assessment Program: Mid Michigan Community College / Barry Alford 4. Designs on Assessment at UNR: University of Nevada, Reno / Jane Detweiler and Maureen McBride 5. Assessment Changes for the Long Haul: Dynamic Criteria Mapping at Indiana University Purdue University Indianapolis / Susanmarie Harrington and Scott Weeden.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Evaluation; English language -- Composition and exercises -- Study and teaching -- Evaluation; College prose -- Evaluation